PHILOSOPHICAL ANALYSIS OF SCIENTIFIC-THEORETICAL CONCEPTS OF CIVIL SOCIETY - Shamsiddinov Burkhanjon Jakbarovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This philosophical analysis explores the scientific-theoretical concepts of civil society and delves into their philosophical implications. It aims to examine the underlying principles and ideas that shape our understanding of civil society and its role in society. The analysis begins by defining civil society and its significance in relation to the state and the individual. It explores the various theoretical perspectives on civil society, including liberal, communitarian, and critical theories, and investigates their philosophical foundations.Furthermore, the analysis delves into the key concepts associated with civil society, such as citizenship, social capital, public sphere, and associational life. It examines how these concepts shape our understanding of civil society and its role in promoting democratic values, social cohesion, and public participation.